Evidence on the Incremental Information Content of Additional Firm Disclosures Made Concurrently with Earnings - Hoskin, Robert E.; Hughes, John S.; Ricks, William E. (Journal of Accounting Research, 1986)
Robert E. Hoskin, John S. Hughes, William E. Ricks, Evidence on the Incremental Information Content of Additional Firm Disclosures Made Concurrently with Earnings, Journal of Accounting Research, Vol. 24, Studies on Alternative Measures of Accounting Income (1986), pp. 1-32